The relationship between career advancement on job performance among women in Sabah - Nur Faizrah Ganie; Borhan Abdullah; Roslinah Mahmud (Universiti Malaysia Sabah, 2024)
The purpose of this study is to identify the relationship between career advancement and job performance among women, as well as to examine the relationship of mediating education on both dependent and independent variables. The reviewof literature indicates that the efforts of women involved in employment have continued to face challenges in career advancement (work-life balance, family responsibilities, and fear of success) and job performance. These barriers canbecomplex, including limitations on the effect of an education. A quantitative research design is conducted throughout aquestionnaire which is formulated from the primary data collection. A total of 40 female employees filled a questionnairegiven in Sabah. Meanwhile, the analysis method used was Smart-PLS version 4 structural equation modeling technique, which is the regression and descriptive methods. The findings of this research believes women due have barriers on career advancement which has affected their job performance, while education proven causes employee career advancement and they believe it has achieved the standard of job performance within the organization. Therefore, this study contributes an important insight into the challenges faced by women in Sabah, expanding the importance of education, and unlocking the potential of women-led employment.